2022
DOI: 10.3390/children9111627
|View full text |Cite
|
Sign up to set email alerts
|

Atrioventricular Block in Celiac Disease: An Unusual Clinical Presentation in a Child. A Case-Based Review

Abstract: Congenital or acquired atrioventricular block (AVB) is a rare disorder in the pediatric population, while celiac disease (CeD) is a common multisystemic autoimmune disorder that is characterized by intestinal manifestations as they are the typical clinical presentation. Sometimes CeD presents more complex multisystemic involvement which includes the heart. Cardiac involvement, such as dilated cardiomyopathy, myocarditis or conduction disease, have been mainly described in untreated adult patients with or witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Aside from CMP, several different cardiac manifestations have also been attributed to the presence of CD [12,[51][52][53]. Rhythm and conduction disturbances such as atrial fibrillation and AV block have all been described in the literature as possible complications of CD [52][53][54], some of which were seen in cases reported in this paper [28,41,55].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Aside from CMP, several different cardiac manifestations have also been attributed to the presence of CD [12,[51][52][53]. Rhythm and conduction disturbances such as atrial fibrillation and AV block have all been described in the literature as possible complications of CD [52][53][54], some of which were seen in cases reported in this paper [28,41,55].…”
Section: Discussionmentioning
confidence: 84%
“…Aside from CMP, several different cardiac manifestations have also been attributed to the presence of CD [12,[51][52][53]. Rhythm and conduction disturbances such as atrial fibrillation and AV block have all been described in the literature as possible complications of CD [52][53][54], some of which were seen in cases reported in this paper [28,41,55]. Moreover, vascular pathology, including accelerated atherosclerosis, thrombosis, and dysregulation of angiogenesis have all been linked to the presence of CD [13,[56][57][58].…”
Section: Discussionmentioning
confidence: 85%
“…A paediatric case of 4-year-old male with acquired progressive atrioventricular block who was diagnosed with celiac disease demonstrated a significant improvement of his conduction abnormality after a strict gluten-free diet. The authors of this case suggested screening for celiac disease in all children with acquired atrioventricular block [ 26 ] .…”
Section: Discussionmentioning
confidence: 99%
“…(7) Presentation patterns with atrioventricular block and syncope, suggesting that the myocardium is affected in CDs, have also been demonstrated in isolated cases. (9,10) In the literature, QTc interval prolongation was observed in one-third of untreated adult CDs, whereas this rate was 3% in patients on a gluten free diet. (11) In the literature there are a lot of studies investigating the relationship of the diet and the ventricular repolarization parameters.…”
Section: Discussionmentioning
confidence: 99%